Misidentification of Mycobacterium fortuitum in an immunocompetent patient presenting with a unilateral neck mass. (17th April 2014) - Kanzara, Todd; Hall, Andy; Namnyak, Simon; Owa, Tony
Abstract : A 31-year-old African man with a blameless medical history presented with an enlarging neck swelling of 6 months duration. He was systemically well with normal heamatobiochemistry. MRI of the neck demonstrated abnormal signalling in the subcutaneous fat overlying the posterior spinal muscles in the midline and the left sternocleidomastoid muscle. Scanty growth of Rhodococcus equi was reported from a turbid fine needle aspirate of the neck on two separate occasions. The swelling progressed despite numerous antibiotic combinations which necessitated surgical debridement. Analysis of debrided tissue using 16S rDNA surprisingly identified Mycobacterium fortuitum, not R equi, thereby resolving our diagnostic conundrum.